AB0469 Evaluation of pilocarpine treatment in xerostomia by pulsed doppler color ultrasonography: echopilo study. (15th June 2017) - Depinoy, T; Saraux, A; Boisrame, S; Cornec, D; Pers, JO; Marhadour, T; Guellec, D; Devauchelle-Pensec, V; Jousse-Joulin, S
Abstract : Background: The ultrasonography of salivary glands (USSG) has proved its utility in diagnosing and following primary Sjögren patient's (pSS) (1, 2). The evaluation of disease activity is still of interest and can be studied by assessing the inflammatory status of SG using US Doppler. Objectives: To evaluate the vascularization of salivary glands, and particularly the parotid gland (PG) using Pulsed Doppler color ultrasonography (USSGPD) in patients complaining of xerostomia before and after treatment by pilocarpine. Methods: We prospectively included patients with objective dry mouth syndrome (using salivary flow rate) at Brest University Hospital (DiapSS cohort). The vascularization was assessed by the resistive index (RI) at the left parotid. Only patients with pathological RI (<0.8) were included in order to observe evolution after pilocarpine. USSGPD was carried out by the same operator. A dental consultation with measure of salivary flows before and after stimulation was performed. These examinations were performed at baseline and after 3 months of treatment with pilocarpine at 4 mg 3 times daily. Results: Among the 19 patients included, 11 received pilocarpine treatment for the whole 3 months period, 6 of the 8 remaining patients stopped the pilocarpine due to side effects. Among the 11 patients with a follow-up evaluation at 3 months, 5 had pSS according to AECG criteria. The differences of RI before and after lemon stimulation were on average of -0.04 at baseline and -0.04 at M3. The sum of ultrasound's grades average of the four glands was 3.47 at M0 and 4.18 at M3. The non-simulated salivary flow was on average of 1.96 mL/mn at M0 and 5.23 mL/mn at M3, whereas the average of stimulated salivary flow was 2.84 mL/mn at M0 and 8.51 mL/mn at M3. None of these observed differences were statistically significant before and after 3 months of treatment by Pilocarpine: RI before and after lemon stimulation (p=0.953), the sum of the four glands' grades (p=0.858), the non-stimulated (p=0.26) and stimulated salivary flow (p=0.139). Concerning the 3 patients with Sjögren's syndrome, there was no differences using RI before and after treatment but the RI was lower in this subgroup compared to the xerostomia patients.The study was marked by a large number of pilocarpine's discontinuation (31%) due to adverse effects. Conclusions: Preliminary results showed no significant differences between the 4 gland's grade, ultrasound's RI and salivary non and stimulated flow before and after three months of pilocarpine's treatment. The vascularisation of salivary glands could be an opportunity to follow our treated patients with Sjögren's syndrome or with xerostomia but more studies are needed to prove the interest of this procedure. References: Cornec D, et al. Contribution of salivary gland ultrasonography to the diagnosis of Sjögren's syndrome: toward new diagnostic criteria? Arthritis Rheum. 2013 Jan;65(1):216–25. Jousse-Joulin S et al. Brief Report: Ultrasonographic Assessment of Salivary Gland Response to Rituximab in Primary Sjögren's Syndrome. Arthritis Rheumatol. 2015 Jun;67(6):1623–8. Acknowledgements: We thank the Professor luc Bressollette and Muriel Korpet for their contribution in the study. Disclosure of Interest: None declared